Coincidence Point Theorems, Intersection Theorems and Saddle Point Theorems on FC-Spaces (Communications in Mathematical Research, 2021)
In this paper, we first give the definitions of finitely continuous topologicalspace and FC-subspace generated by some set, and obtain coincidence point theorem,whole intersection theorems and Ky Fan type matching theorems, and finally discussthe existence of saddle point as an application of coincidence point theorem.
Keywords: FC-space; FC-subspace generated by set; saddle point.